The Neuromodulation of the Intestinal Immune System and Its Relevance in Inflammatory Bowel Disease - Di Giovangiulio, Martina; Verheijden, Simon; Bosmans, Goele; Stakenborg, Nathalie; Boeckxstaens, Guy E.; Matteoli, Gianluca (Frontiers in Immunology, 2015)
One of the main tasks of the immune system is to discriminate and appropriately react to “danger” or “non-danger” signals. This is crucial in the gastrointestinal tract, where the immune system is confronted with a myriad of food antigens and symbiotic microflora that are in constant contact with the mucosa, in addition to any potential pathogens. This large number of antigens and commensal microflora, which are essential for providing vital nutrients, must be tolerated by the intestinal immune system to prevent aberrant inflammation. Hence, the balance between immune activation versus tolerance should be tightly regulated to maintain intestinal homoeostasis and to prevent immune activation indiscriminately against all luminal antigens. Loss of this delicate equilibrium can lead to chronic activation of the intestinal immune response resulting in intestinal disorders such as inflammatory bowel diseases (IBD). In order to maintain homeostasis, the immune system has evolved diverse regulatory strategies including additional non-immunological actors able to control the immune response. Accumulating evidence strongly indicates a bidirectional link between the two systems in which the brain modulates the immune response via the detection of circulating cytokines and via direct afferent input from sensory fibers and from enteric neurons. In the current review we will highlight the most recent findings regarding the cross-talk between the nervous system and the mucosal immune system and will discuss the potential use of these neuronal circuits and neuro-mediators as novel therapeutic tools to re-establish immune tolerance and treat intestinal chronic inflammation.